2012
DOI: 10.1371/journal.pcbi.1002420
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Control of the Binding of the Transactivation Domain of the MLL Protein and c-Myb to the KIX Domain of CREB

Abstract: The KIX domain of CBP is a transcriptional coactivator. Concomitant binding to the activation domain of proto-oncogene protein c-Myb and the transactivation domain of the trithorax group protein mixed lineage leukemia (MLL) transcription factor lead to the biologically active ternary MLL∶KIX∶c-Myb complex which plays a role in Pol II-mediated transcription. The binding of the activation domain of MLL to KIX enhances c-Myb binding. Here we carried out molecular dynamics (MD) simulations for the MLL∶KIX∶c-Myb te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 42 publications
(69 reference statements)
3
42
0
Order By: Relevance
“…Overall, we found that binding of MLL and/or c-Myb resulted in an increase in stability (or a reduction in dynamics) of the α 3 C terminus and the L 12 -G 2 loop. This is consistent with observations made in previous NMR and computational studies, which have led to the suggestion that the increased structural stability of KIX may play a role in allosteric signaling (4,20,(28)(29)(30)(31)(32). For example, NMR backbone order parameter measurements of KIX have demonstrated that the L 12 -G 2 loop and the C-terminal residues of the α 3 helix are more rigid when MLL is bound to KIX (29).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Overall, we found that binding of MLL and/or c-Myb resulted in an increase in stability (or a reduction in dynamics) of the α 3 C terminus and the L 12 -G 2 loop. This is consistent with observations made in previous NMR and computational studies, which have led to the suggestion that the increased structural stability of KIX may play a role in allosteric signaling (4,20,(28)(29)(30)(31)(32). For example, NMR backbone order parameter measurements of KIX have demonstrated that the L 12 -G 2 loop and the C-terminal residues of the α 3 helix are more rigid when MLL is bound to KIX (29).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have observed changes in the KIX structure resulting from transcription factor binding, and both MLL and c-Myb have been shown to allosterically affect the affinity of KIX for the complementary peptide (4,20,(28)(29)(30)(31)(32). However, a connection between the changes in structural dynamics in KIX and how this directly leads to shifts in transcription factor binding affinities remain tenuous.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not surprisingly, 1-10 bound to either mutant affects the residues within and proximal to the pKID binding site. However, 1-10 has a larger overall effect on KIX L664C residues (blue and green), with perturbations distributed not only at both MLL (between helices α 2 and α 3 ) and pKID (between helices α 1 and α 3 ) binding interfaces but also at the loop region, which has been implicated to play an important role in the conformational dynamics of KIX during binding events (12,33,34). The perturbations exhibited at the N terminus of α 3 and the two termini of α 1 are consistent with those observed upon MLL binding to KIX (12).…”
Section: Identification Of Kix Residues Affected In Positive and Negamentioning
confidence: 99%